1973
DOI: 10.1111/j.1365-2141.1973.tb01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Transcobalamins

Abstract: Summary. Vitamin B12 absorbed from the gut is transported on all the vitamin B12 binding proteins (transcobalamins) and not primarily on Transcobalamin II. Absorbed vitamin B12 can still be detected on the vitamin B12 binding proteins after 10 days suggesting that the very rapid plasma clearance of the TCII‐vitamin B12 complex previously reported was probably due to damage to TCII prior to re‐injection. Vitamin B12 binder III is part of Transcobalamin I complex showing immunological identity with other binder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1975
1975
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…As patients with an apparently complete deficiency of TCII suffer from a severe megaloblastic anaemia [14], and as patients with a partial deficiency of TCI seem to have normal erythropoiesis [5], it is generally believed that the B12 binder involved in the transfer of vitamin B12 to tissue cells is TCII and not TCI. This view is also consistent with the observation that vitamin B12 bound to TCI and TCIII clears more slow ly from the circulation than vitamin B,2 bound to TCII [8]. However, the above observations do not completely eliminate the possibility that TCI and TCIII participate in the transfer of some vitamin B12 to tissue cells, particularly as the cases of megaloblastic anaemia associated with TCII deficiency were also complicated by malabsorption of vitamin B12 [14] and by some atypical biochemical features [19].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…As patients with an apparently complete deficiency of TCII suffer from a severe megaloblastic anaemia [14], and as patients with a partial deficiency of TCI seem to have normal erythropoiesis [5], it is generally believed that the B12 binder involved in the transfer of vitamin B12 to tissue cells is TCII and not TCI. This view is also consistent with the observation that vitamin B12 bound to TCI and TCIII clears more slow ly from the circulation than vitamin B,2 bound to TCII [8]. However, the above observations do not completely eliminate the possibility that TCI and TCIII participate in the transfer of some vitamin B12 to tissue cells, particularly as the cases of megaloblastic anaemia associated with TCII deficiency were also complicated by malabsorption of vitamin B12 [14] and by some atypical biochemical features [19].…”
Section: Discussionsupporting
confidence: 78%
“…The sera were saturated with S7Co-vitamin B12 by the addition of 2 ng of ! 'Co-cyanocobalamin (specific ac tivity 100-300 /tCi/,ug)/ml of serum, the unbound vitamin B,2 was removed by di alysis and the samples were then fractionated by a combination of DEAE-cellulosc chromatography and Sephadex G-200 filtration [4,8], Short-term marrow cultures were prepared using marrow aspirates from 7 pa tients with normoblastic erythropoiesis. The freshly-aspirated bone marrow was mixed with 5 ml Hanks' solution containing preservative-free heparin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B12 in human blood is carried by two major transport proteins (5), transcobalamin I (TCI) and transcobalamin II (TCII). TCI carries approximately 75% of the endogenous B12 in human plasma (6) and binds a small portion of B12 newly absorbed from the intestine (7). The functional role of TCI, however, remains unknown since a congenital deficiency of TCI in humans is asymptomatic anid does not result in reduced levels of vitamin B12 in tissues (8).…”
Section: Introductionmentioning
confidence: 99%
“…Recently England et al (14) observed a third substance, which they refered to as TC III, carrying Bn in the early days after absorption. They postulated a transport system consisting of three plasma transport proteins, each picking up free B in the portal blood more or less in proportion to their unsaturated capacities.…”
Section: Introductionmentioning
confidence: 99%